Happiness and the welfare state in times of globalization: A review of empirical findings - Alexander Heß (OrdnungsPolitisches Portal (OPO), 2020)
The welfare state has long been under debate. Besides various theoretical discussions, it has often been empirically investigated regarding its effects on inequality and economic growth. With the advent of the scientific field of happiness research, scholars began to discuss the welfare state's impact on well-being. Furthermore, over the last three decades, scholars have examined empirically the relationship between welfare states and 'happiness' as more and more data have become available. This article aims to review many of the empirical studies that have been conducted in this regard. Methods and findings are presented and discussed. The conclusion is that though that a larger number of studies exists which finds a positive relationship between welfare state efforts and 'happiness', the overall picture is still vague. Further research might help to add clarity by accessing more recent data and by utilizing different survey datasets on 'happiness' as well as by shifting the focus towards understanding different mechanisms how the welfare state influences the well-being of specific subgroups in the population. In addition, research on non-state welfare providers can put state-conducted efforts into perspective and thus help to gain insights into the overall impact of welfare efforts.
Keywords: 330; welfare state; decommodification; social security expenditures; happiness; life-satisfaction; subjective well-being